Connecting Urban and Regional Socio-ecological Transitions: Paths to a Non Fossil Society in the Swedish Stockholm-Malar area. (2017) - Svedin, U.; Borgström, S.; Liljenström, H.
Abstract: Introduction: The embedding of cities in a wider regional frame is central for long term planning regarding the transformation of such parts of society. This holds especially true for urban centers of national or sub national status. In this presentation we are drawing on 4 years of research work and stakeholder consultations in the Swedish part of the EU COMPLEX project dealing with the transition to non fossil societies. In our presentation the regional multi layered governance which encompasses both a large (the Swedish capital) city and its surrounding region with an archipelago of larger and smaller towns is at the heart of the presentation. Our core interest is in the transition to sustainable and resilient urban futures. Especially we are drawing on the experiences from the Swedish case in the EU project COMPLEX. Method: We are relying both on stakeholder consultations with regard to long term planning as well as on specific regional modelling efforts covering specific features as municipality planning, economic regional analysis, land use studies and cognitive analysis regarding decision making by individuals, Results: We have focused on the systemic interactions of many different kinds covering long term developments (up to 2050). Our focus is to analyze features of the transition process of our urban-region at large and the connected decision making features e.g. in terms of scenario elaborations. Discussion: We highlight the differences of opinions among a wide range of stakeholders with regard to their understanding of the issues, their ideological positioning about core matters of concerns and the various positions about appropriate paths for reaching the goals of the transition to a non-fossil urban-super region situation in our chosen case area.